The Study on the Risk Response of Security Cyber Physical System (Focusing on Analysis of Security Access Log and Unstructured Data) - KANG, JangMook; Hee YOON, Cheol; Hyeong KWON, Tae (International Journal of Engineering and Technology, 2018)
Malicious hacking is evolving continuously malicious code attacks. It needs flexible solutions such as the prevention leakage of personal information, demanding the ability of institutions to prevent high level of infringement. But, typical simple's security control system is limited by responding only to the tertiary industry equipment in the ICT field. A CPS type security system is capable of responding to the transition from ICT to AI which is should be applied. This is time of reorganization from the current security domain to the artificial intelligent ICBM device, it should apply the digital twin model which we are considering the people and environment of CPS type system. In this paper, we have studied a model of how cyber - physical systems can be implemented using existing security system platform technology. We also propose a new security technology applying model through analyzing log form of security equipment that has occurred for many years.Â Â